Ewing Sarcoma Presenting as Fever of Unknown Origin (FUO) in Children: A Case Report and Brief Review of the Literature - Hasan Arafat; Zahraa MM Zeer; Almotazbellah MM Zeer; Mahmoud Noman; Hamza A Abdul-Hafez; Ahmad G Hammouri; Amer Zughayyer (Clinical Medicine Insights: Case Reports)
Introduction: Fever of unknown origin is one of the challenging medical conditions with a wide differential diagnosis. Case presentation: We present a case of 16-year-old patient with Ewing sarcoma diagnosed with neoplastic fever. Discussion: Neoplastic fever, which is caused by the tumor itself, is diagnosed when all other causes of fever have been ruled out. It occurs more frequently in hepatic, renal, and hematological cancers. After history and physical examination, a thorough individualized diagnostic approach is required. Removing the underlying cause of fever when feasible and symptomatic relief with NSAIDS are the primary therapeutic approaches. Conclusion: Fever is common in patients with cancer and it can be due to infectious and non-infectious causes. After excluding all potential causes, neoplastic fever is diagnosed.